Prevalence of cardiovascular diseases and drug utilization review at secondary care hospital in South India - Kenchugundu, Jagadeesh; B., Priyanka Padmashali; Divate, Srividya; S., Santhi Jyothi (International Journal Of Community Medicine And Public Health, 2023)
Background: To study prevalence of cardiovascular diseases and drug utilization review in patients with cardiovascular diseases. Methods: This was a cross-sectional study conducted for about 6 months from December 2021 to February 2021 in a Secondary care hospital. Prescriptions of 167 patients with cardiovascular diseases were analysed. Patient Case files were used for extracting necessary data. Results: The collected data was analyzed by MS-Excel (Counts and Percentages).Cardiovascular diseases were most common in the age group of 31-40 years (27.55%) followed by 51-60 years (24.49%) among male patients and in female patients, it was more common in the age group of 41-50 years (23.19%) followed by 51-60 years (21.74%). Most prevalent cardiovascular disease was found to be Hypertension (31%), followed by coronary artery disease (21%) and acute coronary syndrome (19%). Diabetes Mellitus (39%) and Hematological disorders (20%) are the most found co-morbidities along with cardiovascular diseases. Antiplatelet and antihypertensive were the most prescribed category of drugs. Of all Cardiovascular drugs, Aspirin (115 prescriptions) followed by Clopidogrel (100 prescriptions), Atorvastatin (73 prescriptions), Olmesartan (54 prescriptions) and Metoprolol (49 cases) were mostly prescribed. Common combinations of drugs prescribed are Aspirin + Clopidogrel + Atorvastatin (25%) followed by Aspirin + Clopidogrel (24%). Out of the total 658 drugs prescribed, 15.95% (105) were from Essential Drug List of India (2011). Of the total drugs prescribed, 15.95% (105) were from Essential Drug List of India. Conclusions: The present study concluded that most of the drugs were prescribed rationally according to current guidelines. Combination therapy found to have an implication for the good cardiovascular outcome on long term follow-up.